Did You Enjoy It? The Role of Intensity-Trait Preference/Tolerance in Basic Psychological Needs and Exercise Enjoyment - Teixeira, Diogo S.; Rodrigues, Filipe; Machado, Sérgio; Cid, Luis; Monteiro, Diogo (Frontiers in Psychology, 2021)
Promoting exercise regimens that aim at enhancing the quality of individuals’ subjective exercise experience can be challenging. Given the recent theoretical contributions regarding the possible interaction of exercise intensity-traits and several motivational variables, as well as their potential value for exercise adherence, the objective of this study was to examine the mediation role of basic psychological needs in the relationship between preference for and tolerance of exercise intensity and enjoyment. This cross-sectional study comprised a total of 160 exercisers (Mage = 34.12; SD = 9.23; 73 males) enrolled in several health clubs. All analyses were performed using SPSS v. 23.0/PROCESS v. 3.4. The results indicate that intensity-traits presented positive associations with enjoyment, and negative associations with all of need frustration variables. A mediation role of needs frustration emerged in the intensity-traits and enjoyment associations that was analyzed according to relatable theoretical considerations.